1994
DOI: 10.1021/bi00186a030
|View full text |Cite
|
Sign up to set email alerts
|

ATP Binding in Peptide Synthetases: Determination of Contact Sites of the Adenine Moiety by Photoaffinity Labeling of Tyrocidine Synthetase 1 with 2-Azidoadenosine Triphosphate

Abstract: Characterization of the nucleotide binding domain in peptide synthetases was approached by photoaffinity labeling of tyrocidine synthetase 1 (TY1) with 2-azidoadenosine triphosphate (2-azido-ATP). Exposure of TY1 in the presence of photolabel to irradiation with ultraviolet light resulted in a time-dependent covalent modification of the enzyme with a concomitant loss of catalytic activity. Inactivation was not observed if incubation was performed in the absence of either light or the nucleotide analogue. Speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…The lysine residue of the PPS I motif (NGK), which has been shown to be involved in ATP binding (28), is not conserved in the SnbA family, but several other lysines (512, 530, 533, and 534 as numbered in the alignment) are conserved in the neighboring region. Core sequence H, thought to be involved in adenine binding (29), is not found in the EntE subfamily.…”
Section: Resultsmentioning
confidence: 98%
“…The lysine residue of the PPS I motif (NGK), which has been shown to be involved in ATP binding (28), is not conserved in the SnbA family, but several other lysines (512, 530, 533, and 534 as numbered in the alignment) are conserved in the neighboring region. Core sequence H, thought to be involved in adenine binding (29), is not found in the EntE subfamily.…”
Section: Resultsmentioning
confidence: 98%
“…The C domain is responsible for peptide bond formation in nonribosomal peptide biosynthesis. (14,41,42,56). Analysis of other peptide synthetases has indicated that each activation domain is responsible for activation of a single amino acid.…”
Section: Resultsmentioning
confidence: 99%
“…Specific activities were calculated from luciferase protein values determined by Western blot analysis and are reported relative to the value obtained at pH 7.8 for each protein: WT (E), L194F/M196L (Ç), S198T (ϫ), L194F/S198T (ϩ), L194F/N197Y/S198T (ࡗ), and L194Y/M196L/S198T/S201T (ᮍ). (16), but now that the luciferase structure is available (10), it can readily be seen that sites of photoaffinity labeling are spatially close to 198 -207 even though they are distant in the primary structure. This region of the protein likely constitutes a portion of the ATP binding domain.…”
Section: Resultsmentioning
confidence: 99%